Inhibition of colorectal cancer cell proliferation, invasion, and migration, and induction of epithelial-mesenchymal transition via TFF1 silencing - Zhao, Jing; Wang, Fan; Li, Miao; Liang, Rui; Li, Changying; Li, Menglong; Yalikun, Dilimulati; Wang, Zhiqiang (Vojnosanitetski pregled, 2025)
Background/Aim. The identification of aberrant genes associated with colorectal cancer (CRC) and understanding their pathogenic mechanisms are important for early diagnosis and the determination of appropriate therapy. The aim of this study was to examine the impact of trefoil factor 1 (TFF1) on the proliferation, invasion, and migration of CRC cells. Methods. The expression of TFF1 in 40 CRC tissue samples was assessed using immunohistochemistry. Additionally, the expression of TFF1 in CRC cell lines HCT116 and Caco-2 was determined using real-time quantitative polymerase chain reaction (qPCR) and Western blot analysis. Then the Caco-2 cell line was transfected with a lentivirus-packaged small interfering ribonucleic acid to silence TFF1 expression. The cell counting kit-8 assay and cell colony formation assay were used to assess cell proliferation and colony formation capacity, while the Transwell assay and wound healing assay were used to assess cell invasion and migratory ability. Subsequently, the expression levels of E-cadherin and vimentin were assessed using qPCR and Western blotting to study the relationship between TFF1 expression and epithelial-mesenchymal transition. Results. The positive rate of TFF1 expression in CRC tissues was 35% (14/40). The HCT116 cell line demonstrated modest levels of TFF1 expression, while the Caco-2 cell line exhibited significant levels. Caco-2 cells expressed less TFF1 messenger ribonucleic acid and protein after TFF1 silencing. The proliferative and colony-forming powers of Caco-2 cells, as well as their invasion and migratory capabilities, were subsequently seen to decrease. Furthermore, silencing TFF1 expression led to an increase in E-cadherin expression and a decrease in vimentin expression. Conclusion. Caco-2 CRC cells can be inhibited from proliferating, migrating, and invading by silencing TFF1 expression. TFF1 may play a significant role in the initiation, development, and metastasis of CRC by promoting epithelial-mesenchymal transition.